Downshifting Yeast Dominance: Cell Physiology and Phospholipid Composition Are Altered With Establishment of the [GAR+] Prion in Saccharomyces cerevisiae - Walker, Gordon A.; Henderson, Clark M.; Luong, Peter; Block, David E.; Bisson, Linda F. (Frontiers in Microbiology, 2020)
Establishment of the [GAR+] prion in Saccharomyces cerevisiae reduces both transcriptional expression of the HXT3 hexose transporter gene and fermentation capacity in high sugar conditions. We evaluated the impact of deletion of the HXT3 gene on the expression of [GAR+] prion phenotype in a vineyard isolate, UCD932, and found that changes in fermentation capacity were observable even with complete loss of the Hxt3 transporter, suggesting other cellular functions affecting fermentation rate may be impacted in [GAR+] strains. In a comparison of isogenic [GAR+] and [gar-] strains, localization of the Pma1 plasma membrane ATPase showed differences in distribution within the membrane. In addition, plasma membrane lipid composition varied between the two cell types. Oxygen uptake was decreased in prion induced cells suggesting membrane changes affect plasma membrane functionality beyond glucose transport. Thus, multiple cell surface properties are altered upon induction of the [GAR+] prion in addition to changes in expression of the HXT3 gene. We propose a model wherein [GAR+] prion establishment within a yeast population is associated with modulation of plasma membrane functionality, fermentation capacity, niche dominance, and cell physiology to facilitate growth and mitigate cytotoxicity under certain environmental conditions. Down-regulation of expression of the HXT3 hexose transporter gene is only one component of a suite of physiological differences. Our data show the [GAR+] prion state is accompanied by multiple changes in the yeast cell surface that prioritize population survivability over maximizing metabolic capacity and enable progeny to establish an alternative adaptive state while maintaining reversibility.